2014
DOI: 10.1542/peds.2014-0329
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age and Age at Sampling Influence Metabolic Profiles in Premature Infants

R. H. Clark,
A. S. Kelleher,
D. H. Chace
et al.

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Prematurely born infants commonly have abnormal metabolic screens.WHAT THIS STUDY ADDS: Both gestational and chronological age influence metabolic profiles used to screen for inborn errors of metabolism.abstract OBJECTIVE: To describe the influence that gestational age and chronological age have on amino acid and acylcarnitine profiles in an atrisk population of premature infants. METHODS:Metabolic profiles (15 amino acids and 35 acylcarnitines) were obtained by using standard new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 13 publications
2
38
2
7
Order By: Relevance
“…It is possible that metabolic immaturity may contribute to dysfunctional FAO in premature neonates since false-positive newborn screens are more common in premature and low-birth-weight infants, 38 but this association has been found mainly for disorders of amino acid and hormone metabolism rather than FAO disorders. 39, 40 We do not yet know where dysfunctional FAO lies on the causal pathway for preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that metabolic immaturity may contribute to dysfunctional FAO in premature neonates since false-positive newborn screens are more common in premature and low-birth-weight infants, 38 but this association has been found mainly for disorders of amino acid and hormone metabolism rather than FAO disorders. 39, 40 We do not yet know where dysfunctional FAO lies on the causal pathway for preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,[19][20][21][22][23] This study shows a new NBS blood collection, the 3-hour stop-PN protocol, can significantly reduce falsepositive AA results and the associated medical costs. The current study confirms and expands the results of a smaller study of the effect of holding AA containing PN by Morris et al 23 The current study includes a much larger sample size of VLBW infants (87 vs 413 in this study).…”
Section: Discussionmentioning
confidence: 81%
“…Several studies have identified factors associated with false-positive NBS, one of the most significant of which is prematurity and low BW. [6][7][8][9] Our study focused on AA results in NBS, which are among the most common false-positive NBS results. The false-positive rate for AA was 0.3% of total newborn infants, and approximately 90% of infants with false-positive AA results are VLBW infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking at home, smoking during pregnancy, eczema, asthma and atopic family history did not show any correlation. For UBD only, a correlation with gestational age was found; however, gestational age is a well-known confounder, which does not exclude the value of UBD as severity marker [23].…”
Section: Gene Expression Validationmentioning
confidence: 85%